Iklan Game 8 Ball Pool dan Pengetahuan Produk (Studi Deskriptif Kualitatif Pada Gamers di Medan) - Taufiq Athwinsa (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
The research is titled as 8 Ball Pool Game Advertisement and Product Knowledge (Qualitative Descriptive Study on gamers in Medan) that focuses on the effectiveness of the advertisement in 8 Ball Pool game and the product knowledge. The goal is to know the effectiveness of advertisement in 8 Ball Pool and knowledge of informants of the product. This research uses qualitative methodology in descriptive form. Data collection techniques are done by doing in-depth interviews to 8 Ball Pool game players. Research subjects in this study contains five informants, with the names: Ampang Sagala, Willy, Ryan Aprilliandi, Hasbi Aulia, and Asril. Data analysis techniques, by reducing data, presenting data and drawing conclusions. The research was done in July 19, 2017 until August 20, 2017. The findings of this research indicates several types of adverts presented from 8 ball pool to its users such as online game advertising and products or services. The ads can be seen by the players of the 8 Ball Pool online game is ineffective in attracting users of 8 ball pool online games to buy and download the advertised products.